The reality of the application of social responsibility among the companies of the Saudi telecom sector during the Corona pandemic (Covid-19) - Alotibi, Fawziah Rashed; Aljaeed, Samia Ayed (Journal of Economic, Administrative and Legal Sciences, 2024)
The Kingdom of Saudi Arabia’s Vision 2030 aims to pay widespread attention to the issue of social responsibility and its effective role in sustainable development, as it is the first line of defense against any danger threatening the individual or society. From this standpoint came the idea of research. Which aims to discover the reality of implementing social responsibility among companies in the Saudi telecommunications sector during the Corona pandemic, and to know the extent to which companies are aware of the importance of their social responsibility, especially in times of crisis. The descriptive analytical approach was relied upon, with the use of a questionnaire as a tool for collecting data from members of the research sample. This research was applied to a sample of employees working in the Saudi Telecommunications sector in the city of Mecca, and the sample size is (72) employees. . The research reached a set of results, the most prominent of which are: a high degree of implementation and commitment from Saudi telecom companies in the Holy City of Mecca to their social responsibility during the Corona pandemic towards their employees and towards society and the state. The research reached a set of recommendations, most notably: the necessity of establishing an infrastructure for social responsibility, and developing strategies and action plans in times of crises. Preparing a legislative system to enhance companies’ social responsibility.